'We have never been behaviourally modern': The implications of Material Engagement Theory and Metaplasticity for understanding the Late Pleistocene record of human behaviour. (16th June 2016) - Roberts, Patrick
Abstract: The emergence of the human mind is a topic that has been of considerable interest to the disciplines of archaeology, cognitive archaeology and neuroscience in recent years. Most research in this regard has tended to focus on what material culture associated with early Homo sapiens might reflect in terms of the timing and nature of early cognitive capacities and 'behavioural modernity'. In recent years, however, both the concept of 'behavioural modernity' and its passive treatment of material culture have become highly criticised. Yet, until now, there has remained some confusion as to where to turn in its absence. Recently, Lambros Malafouris outlined the theoretical frameworks of Material Engagement Theory and Metaplasticity as a means to understand the active role of material culture in the constitution of the human mind. However, despite Malafouris' application of these theoretical frameworks to a series of case studies previously associated with human cognitive 'modernity' (including tool manufacture, early body ornamentation, and ritual art), the Late Pleistocene archaeological community has done little to engage with this work. In this paper I outline and then apply MET and Metaplasticity to two further case studies often considered pertinent to the development of human cognition in the Late Pleistocene – namely, long-distance resource sourcing and/or exchange and the development of composite technologies. In doing so, I hope to demonstrate that there is somewhere to turn in the wake of the statement 'we have never been behaviourally modern'.